Analisis Perilaku Pedagang Buah Dalam Perspektif Etika Bisnis Islam di Pasar Buah Simpang Sado Kota Jambi - Arbi Martin; Ambok Pangiuk; Ogi Saputra (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Islamic business ethics are provisions of ethical norms in doing business based on the Qur'an and Hadist which should be used as a guideline for doing business by a businessman. But in fact what is found in the field are many unscrupulous business people who have not properly implemented Islamic business ethics. This study discusses the analysis of the behavior of fruit sellers in the perspective of Islamic business ethics at the Sado intersection fruit market, Jambi city. The purpose of this study is to describe how the behavior of fruit traders at the Simpang Sado fruit market in Jambi city in the perspective of Islamic business ethics.This research is a field research using descriptive qualitative method. Collecting data by conducting observations, interviews and documentation. Test the validity of this study with triangulation techniques. The subjects in this study were fruit traders and buyers.The results of this study indicate that fruit traders at the Simpang Sado Fruit Market, Jambi City, have not fully implemented good Islamic business ethics in their business. This can be seen from the five principles of Islamic Business Ethics, namely the Principles of Monotheism, Balance, Free Will, Responsibility and Ihsan. Of the five principles, only the principle of free will and the principle of responsibility have been implemented properly. However, the principle of monotheism, the principle of balance and the principle of ihsan, has not been fully implemented properly. Such as obedience in worship, fairness in service, fairness in determining prices, maintaining quality, honesty and transparency. Therefore, the behavior of fruit traders at the Simpang Sado Fruit Market, Jambi City, is not fully appropriate based on the perspective of Islamic Business Ethics. As for the impact of traders' misunderstanding of Islamic business ethics in buying and selling transactions, it has a negative impact on buyers, because buyers feel aggrieved by the actions of traders who deviate from Islamic business ethics.